Molecular Mechanisms of Cardiomyocyte Death in Drug-Induced Cardiotoxicity - Ma, Wanjun; Wei, Shanshan; Zhang, Bikui; Li, Wenqun (Frontiers in Cell and Developmental Biology, 2020)
Homeostatic regulation of cardiomyocytes plays a crucial role in maintaining the normal physiological activity of cardiac tissue. Severe cardiotoxicity results in cardiac diseases including but not limited to arrhythmia, myocardial infarction and myocardial hypertrophy. Drug-induced cardiotoxicity limits or forbids further use of the implicated drugs. Such drugs that are currently available in the clinic include anti-tumour drugs (doxorubicin, cisplatin, trastuzumab, etc), antidiabetic drugs (rosiglitazone and pioglitazone) and an antiviral drug (zidovudine). This review focused on cardiomyocyte death forms and related mechanisms underlying clinical drug-induced cardiotoxicity, including apoptosis, autophagy, necrosis, necroptosis, pryoptosis and ferroptosis. The key proteins involved in cardiomyocyte death signaling were discussed and evaluated, aiming to provide a theoretical basis and target for the prevention and treatment of drug-induced cardiotoxicity in the clinical practice.